2020
DOI: 10.3389/fphar.2020.01303
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Alters the Activity of Liver Cytochromes P450 in Mice With Sex-Dependent Differences

Abstract: Sexual differences and the composition/function of the gut microbiome are not considered the most important players in the drug metabolism field; however, from the recent data it is obvious that they may significantly affect the response of the patient to therapy. Here, we evaluated the effect of microbial colonization and sex differences on mRNA expression and the enzymatic activity of hepatic cytochromes P450 (CYPs) in germ-free (GF) mice, lacking the intestinal flora, and control specific-pathogen-free (SPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Our findings that Cyp3a11 mRNA expression and enzyme activity of CYP3A were lower in GF than SPF mice are in line with our previous studies [ 30 , 31 ], showing that the presence of microbiome is crucial in the synthesis of CYP3A. However, it is not clear if this phenomenon contributes to more efficient metabolism of metronidazole in SPF mice.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings that Cyp3a11 mRNA expression and enzyme activity of CYP3A were lower in GF than SPF mice are in line with our previous studies [ 30 , 31 ], showing that the presence of microbiome is crucial in the synthesis of CYP3A. However, it is not clear if this phenomenon contributes to more efficient metabolism of metronidazole in SPF mice.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, it was found that colonization by only a single non-pathogenic or probiotic bacteria strain alters the mRNA expression of some hepatic CYPs in originally GF mice [ 30 ]. Results of other studies have highlighted the role of gut microbiome and its metabolites in the regulation of CYPs expression, along with other factors [ 31 , 32 ]. Drug administration may also contribute into this complex equation and influence the expression of CYPs, differently in the GF and SPF mice.…”
Section: Discussionmentioning
confidence: 99%
“…Jourova et al found that the degree of APAP liver injury in germ-free (GF) mice or mice cleared of gut microbiota was lower than in SPF mice. The expression of the P450 enzyme, which is involved in APAP metabolism in the liver, is closely linked to intestinal microorganisms (Jourova et al, 2020 ). The expression levels of CYP-1A2 and CYP-3A4 in the liver of GF mice were significantly lower than in SPF mice, which may explain the significant reduction of APAP-induced hepatotoxicity in GF mice (Jourova et al, 2020 ).…”
Section: The Gut Microbiota and Apap-induced Liver Injurymentioning
confidence: 99%
“…The expression of the P450 enzyme, which is involved in APAP metabolism in the liver, is closely linked to intestinal microorganisms (Jourova et al, 2020 ). The expression levels of CYP-1A2 and CYP-3A4 in the liver of GF mice were significantly lower than in SPF mice, which may explain the significant reduction of APAP-induced hepatotoxicity in GF mice (Jourova et al, 2020 ). Meanwhile, single-cell sequencing data showed that there were significantly fewer LY6C -positive monocytes and a lower proportion of activated non-parenchymal cells (hepatic stellate cells, sinusoidal endothelial cells, and Kupffer cells) in the liver of antibiotic-treated mice compared with SPF mice.…”
Section: The Gut Microbiota and Apap-induced Liver Injurymentioning
confidence: 99%
“… 54 Interestingly, sex differences in the effects of the microbiome on mRNA expression of liver CYP3A have been found in mice. 55 …”
Section: Discussionmentioning
confidence: 99%